2017
DOI: 10.1371/journal.pone.0183339
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiotherapy reduces gastrointestinal toxicity in pelvic radiation therapy with moderate dose

Abstract: This retrospective study was performed to evaluate and compare gastrointestinal (GI) toxicities caused by conventional radiotherapy (cRT) and intensity modulated radiotherapy (IMRT) in 136 cancer patients treated with pelvic radiotherapy (RT) with moderate radiation dose in a single institution. A matched-pair analysis of the two groups was performed; each group included 68 patients. Conventional RT was delivered using the four-field box technique and IMRT was delivered with helical tomotherapy. The median dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 32 publications
3
14
0
1
Order By: Relevance
“…[8,9] Modern techniques, such as IMRT and IGRT, can deliver smaller irradiation doses to the small bowel, resulting in less acute gastrointestinal toxicities in patients receiving pelvic RT. [10,11] The NRG/RTOG 1203 study showed that pelvic IMRT for cervical and endometrial cancer was related with significantly less gastrointestinal and urinary Abbreviations: CI confidence interval, SD standard deviation, V scan bladder volume measurement using bladder scan, V ratio bladder volume measurement using ratio of anatomical features toxicities than was standard RT, based on patientreported toxicities according to the Expanded Prostate Cancer Index Composite [10]. Despite this, 33.7% of patients receiving IMRT still developed frequent or almost constant diarrhea in the NRG/RTOG 1203 study.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] Modern techniques, such as IMRT and IGRT, can deliver smaller irradiation doses to the small bowel, resulting in less acute gastrointestinal toxicities in patients receiving pelvic RT. [10,11] The NRG/RTOG 1203 study showed that pelvic IMRT for cervical and endometrial cancer was related with significantly less gastrointestinal and urinary Abbreviations: CI confidence interval, SD standard deviation, V scan bladder volume measurement using bladder scan, V ratio bladder volume measurement using ratio of anatomical features toxicities than was standard RT, based on patientreported toxicities according to the Expanded Prostate Cancer Index Composite [10]. Despite this, 33.7% of patients receiving IMRT still developed frequent or almost constant diarrhea in the NRG/RTOG 1203 study.…”
Section: Discussionmentioning
confidence: 99%
“…Although results from comparative randomized clinical trial are not available yet, IMRT is usually associated with less dose to organ at risk, such as urinary bladder, small bowel and anal sphincters (in selected cases). This is translated into better clinical outcomes, in terms of gastrointestinal toxicity, genitourinary toxicity and skin side effects [16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…Brachytherapy (BT) as a boost to external beam radiotherapy (EBRT) is the gold standard in the curative management of locally advanced cervical cancer and significantly improves survival [2,3,4]. In the last decades, the development of intensity-modulated radiotherapy (IMRT) has resulted in the reduction of acute and chronic toxicity in pelvic radiotherapy compared to conventional three-dimensional (3D) conformal radiotherapy (CRT), with the same oncological outcome [5,6,7,8,9]. Concern-ing BT, radiation therapy centres around the world transited from low-dose-rate (LDR) to remote after-loading high-dose-rate (HDR) keeping the same oncological result, as demonstrated in a number of randomized trials [10,11,12,13,14,15,16].…”
Section: Purposementioning
confidence: 99%